Léxico toponímico do Médio Jequitinhonha-MG: reflexo de aspectos históricos e socioculturais - Shirlene Aparecida da Rocha (2023)
Considering the different levels of language, the lexicon is the most reliable means of revealing the culture of a society. It reflects the way the community sees the world, both physically, through words that reflect its view of the environment, and psychologically, through terms that represent its beliefs, customs, desires, and so on. The objective of this study was to describe the toponymic lexicon of the Middle Jequitinhonha Valley, which is located in the northeast of Minas Gerais, in an area covered by caatingas, cerrados and Atlantic forest spread over mountains, tablelands and large open valleys, situated mostly in the domain of the Semiarid Region. The names of rural communities, districts, farms, villages, rivers, streams, brooks, dams, waterfalls, and mountain ranges constituted the corpus to investigate how the relationship between language and culture is represented in the toponymic field. As a theoretical contribution, works from the field of Lexicology were used, whose main authors are Sapir (1969), Ullmann (1974), Biderman (1981, 1998, 2001), Dauzat (1926), Stewart (1954), Dick (1986, 1990 to 1990b, 1996), Seabra (2004, 2008, 2010, 2015), Isquerdo (1996, 1998, 2012, 2019), Castro (2018), Carvalhinhos (2007, 2009) Amaral (2013, 2020), and Duranti (2000). To this end, we delimited the geographical area designated by the IBGE (Brazilian Institute of Geography and Statistics) in 2017 as the Immediate Geographic Region of Araçuaí, which includes the municipalities of Araçuaí, Berilo, Coronel Murta, Francisco Badaró, Itinga, Jenipapo de Minas, José Gonçalves de Minas, and Virgem da Lapa. The 252 toponyms analyzed were collected through 24 semi-structured interviews, three in each municipality within the research area, in addition to the use of geographic maps and official documents provided by the respective municipalities. The results showed a conservative toponymy, in which only 5.15% of the toponyms underwent changes by substitution. Regarding origin, toponyms of Portuguese origin prevailed with 80%, those of indigenous origin totaled 16%, those of African origin accounted for 2%, and the others corresponded to 2%. As for the morphological structure, there was a slight predominance of toponyms with a simple structure, with 54%, in relation to compound toponyms, which added up to 46%. The five most recurrent taxa were hydrotoponyms (22%), phytotoponyms (22%), hierotoponyms (12%), anthropotoponyms (11%), and geomorphotoponyms (9%). Data analysis showed that place names in the Middle Jequitinhonha, as in other regions, are created, recreated, adapted or modified depending on the context in which they were inserted in a given period, reflecting historical and sociocultural aspects of a region.